2010
DOI: 10.1590/s0100-736x2010000300002
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicação experimental por Brachiaria decumbens em ovinos confinados

Abstract: Brachiaria decumbens was fed as exclusive source of food to feedlot sheep. Sheep were evaluated in three periods of the year, of 60 days each, regarding their clinical status and was performed collection of blood samples to measure enzymatic activity of gamma glutamyltransferase and aspartate aminotransferase to evaluate their diagnostic importance and usefulness besides the clinical signs, necropsy and histopathology finds in hepatogenous photosensitization Brachiaria related. Out of 24 feedlot sheep, five di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
21

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 16 publications
1
11
0
21
Order By: Relevance
“…animals from herds that have never had contact with the Brachiaria grasses are more susceptible than those created in this pastures (Lemos et al 1996, Oliveira et al 2012.Perhaps this genetic resistance observed in animals raised in Brachiaria pasture is due to reducing of the mechanism of the toxic effect of the plant such as greatermetabolization capacityand degradation of toxic principle ) and adaptation of ruminal microbiota (Albernaz et al 2010). Moreover, it has been proven the existence of individual sensitivity to intoxication (Saturnino et al 2010. For these reasons, explained a relatively small number of animals have been affected by intoxication in this property.…”
Section: Discussionmentioning
confidence: 99%
“…animals from herds that have never had contact with the Brachiaria grasses are more susceptible than those created in this pastures (Lemos et al 1996, Oliveira et al 2012.Perhaps this genetic resistance observed in animals raised in Brachiaria pasture is due to reducing of the mechanism of the toxic effect of the plant such as greatermetabolization capacityand degradation of toxic principle ) and adaptation of ruminal microbiota (Albernaz et al 2010). Moreover, it has been proven the existence of individual sensitivity to intoxication (Saturnino et al 2010. For these reasons, explained a relatively small number of animals have been affected by intoxication in this property.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are circumstantial evidences that genetics play an important role in the resistance to this toxicosis (Riet-Correa et al 2011) and different degrees of individual susceptibility have been demonstrated (Castro et al 2007, Saturnino et al 2010, Faccin et al 2014), up to date there were no reported studies comparing descendants lambs from susceptible and resistant progenitors in relation to Brachiaria spp. poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…poisoning (Brum et al 2007, Castro et al 2007, Saturnino et al 2010, Albernaz et al 2010, Mustafa et al 2012, Oliveira et al 2012, Faccin et al 2014.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations